PENGARUH TOTAL ASET, EXPENSE RATIO DAN PORTOFOLIO TURNOVER TERHADAP KINERJA REKSADANA SAHAM DI INDONESIA - Lidyah, Rika (I-Economics, 2017)
Purpose of this research is to explain emphiris evidence of total assets effect, expense ratio and turnover portfolio to stock mutual funds performance in Indonesia. Sample in this research using purposive sampling method with stock mutual funds official in Otoritas Jasa Keuangan  and Bursa Efek which is still active on Januari 2013 until Desember 2015 as a criteria. Amount of this sample is 184 mutual funds.  Data analysis in this research using multiple linier regression analysis with SPSS. Data analysis result showed that as a simultan has an effect significantly between total assets, expense ratio dan turnover portfolio to stock mutual funds performance in Indonesia 2013-2015 period. If so, total assets, expense ratio dan turnover portfolio have increased and stock mutual funds do. But, as a partial has no effect significantly between total assets, expense ratio and turnover portfolio variable to stock mutual funds performance in Indonesia 2013-2015 period